2022
DOI: 10.3889/oamjms.2022.8431
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Neuron-specific Enolase Serum Levels with Lesion Volume and Clinical Outcome in Acute Stroke Patients

Abstract: BACKGROUND: Neuron-specific enolase (NSE) is released in the cerebrospinal fluid and bloodstream in response to brain damage. Serum NSE levels can be used as a marker of brain nerve cells either in ischemic or hemorrhagic stroke, associated with lesion volume and functional outcome. AIM: The aim of the study was to evaluate the correlation between NSE serum level with lesion volume and functional outcome in acute stroke patients. METHODS: A cross-sectional study was conducted on 29 patients with ischemic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…In addition, a significant correlation between serum NSE level and NIHSS score in ischemic stroke (r = 0.216, p < 0.023) was found in this study, which is similar to Nasution et al [ 19 ]. The results indicated that the serum NSE level in AIS patients was positively correlated with the severity of the disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, a significant correlation between serum NSE level and NIHSS score in ischemic stroke (r = 0.216, p < 0.023) was found in this study, which is similar to Nasution et al [ 19 ]. The results indicated that the serum NSE level in AIS patients was positively correlated with the severity of the disease.…”
Section: Discussionsupporting
confidence: 91%
“…Using the developmental cohort of the forward-looking and continuous hospital stroke registry at the First Affiliated Hospital of Wenzhou Medical University, we have established a nomogram based on age, the NIHSS, PT and serum NSE levels, which was constructed to explore the underlying influence of NSE in the prediction of functional outcomes. While high NSE serum levels in the acute phase were associated with poor outcomes in stroke patients were confirmed in previous research [ 19 ], this is the first study to explore the relationship between serum NSE levels and long-term prognosis of acute ischemic stroke in hypertension patients.…”
Section: Discussionsupporting
confidence: 78%
“…NSE levels were measured in blood samples taken between 12 and 48 h after symptom onset, and NSE has positively correlated to the neurological outcome in stroke patients ( González-García et al, 2012 ). In CSF and blood samples taken from both ischemic and hemorrhagic stroke patients, NSE was identified between four and 8 hours after symptom onset ( Nasution and Bangun, 2022 ). NSE levels positively correlated with functional outcomes assessed using the NIHSS and mRS at 14 days post-stroke ( Nasution and Bangun, 2022 ).…”
Section: Brain-derived Biomarkers (Neuronal and Glial Biomarkers)mentioning
confidence: 99%
“…In CSF and blood samples taken from both ischemic and hemorrhagic stroke patients, NSE was identified between four and 8 hours after symptom onset ( Nasution and Bangun, 2022 ). NSE levels positively correlated with functional outcomes assessed using the NIHSS and mRS at 14 days post-stroke ( Nasution and Bangun, 2022 ). In blood samples taken within the first 48 h after ischemic stroke, high NSE levels were correlated with the severity of neurological symptoms, assessed by the NIHSS ( Kurakina et al, 2021 ).…”
Section: Brain-derived Biomarkers (Neuronal and Glial Biomarkers)mentioning
confidence: 99%
“…In cases of ischemic or hemorrhagic stroke neuron specific enolase concentrations can serve as an indication for brain's nerve cells. Immediately following hemorrhagic or ischemic brain injury, cerebrospinal fluid (CSF) and blood show rising NSE levels (11) . Following an ischemic stroke and other brain tissue traumas like intracerebral hemorrhage, head injury and subarachnoid hemorrhage, NSE concentrations rise in the CSF.…”
Section: Introductionmentioning
confidence: 99%